2015
DOI: 10.1155/2015/187616
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Researches on Long-Term Strength of Granite Gneiss

Abstract: It is important to confirm the long-term strength of rock materials for the purpose of evaluating the long-term stability of rock engineering. In this study, a series of triaxial creep tests were conducted on granite gneiss under different pore pressures. Based on the test data, we proposed two new quantitative methods, tangent method and intersection method, to confirm the long-term strength of rock. Meanwhile, the isochronous stress-strain curve method was adopted to make sure of the accuracy and operability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Granite gneiss is a candidate material for underground oil, CO 2 and shale gas storage and radioactive waste disposal, because of its low permeability (Liu and Xu 2015;Tsang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Granite gneiss is a candidate material for underground oil, CO 2 and shale gas storage and radioactive waste disposal, because of its low permeability (Liu and Xu 2015;Tsang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Szczepanik et al 44 found that dilatancy occurred when the loading was 70-80% of the uniaxial compressive strength, and this stress point can be regarded as its LTS. Generally, the determining method can be classified as (1) unsteady deformation method 45 ; (2) the stress threshold method (σ cd ) 46,47 ; and (3) the isochronal stress-strain curves method (ISSCM) according to the creep experimental results [48][49][50] . www.nature.com/scientificreports www.nature.com/scientificreports/ To better understand the influence of stress level on the long-term strength, the isochronal stress ratio-strain curves of the intact specimen and fissured rock with various fissure dip angles are plotted in Fig.…”
Section: Lts Of Red Sandstone Containing a Single Fissure Lts Is An mentioning
confidence: 99%
“…To solve the problem mentioned above, Liu and Xu [35] introduced a method named intersection method of steady creep rate based on the steady-state rate method. With this method, the stress value corresponding to the intersection point between the fitted curves of steady-state axial strain rate and steady-state volumetric strain rate under different levels of deviatoric stress is defined as the long-term strength of rocks.…”
Section: Long-term Strengthmentioning
confidence: 99%